A Constitutional Turn for Deliberative Democracy in Europe? - Suiter, Jane; Reuchamps, Min (ECPR Press, 2016)
In recent years, public authorities and civil-society organisations, driven by increasing public disengagement and a growing sense of distrust between the public and their representatives, have been instituting exercises in public deliberation, often using ‘mini-publics’, that is relatively small groups of citizens, selected according to various criteria and representing different viewpoints, brought together to deliberate on a particular issue. From small-scale experiments, mini- publics have recently taken a constitutional turn, at least in Europe. Iceland and Ireland have turned to deliberative democracy to reform their constitutions. Estonia, Luxembourg and Romania have also experienced constitutional processes in a deliberative mode. In Belgium, the G1000, a citizen-led initiative of deliberative democracy, has fostered a wider public debate about the place and role of citizens in the country’s democracy. At the same time, the European Union institutions have introduced different forms of deliberative democracy as a way to reconnect with citizens. These empirical cases are indicative of a possible ‘constitutional turn’ in deliberative democracy in Europe. These examples of constitution-making happened in a particular time and place but they may also serve as models for other events.